Screen time and adolescents' mental health before and after the COVID-19 lockdown in Switzerland: A natural experiment - Marciano, Laura; Viswanath, Kasisomayajula; Morese, Rosalba; Camerini, Anne-Linda (Frontiers in Psychiatry, 2022)
Background During the COVID-19 lockdown in 2020, adolescents' mental health was largely undermined. A general increment in screen time was reported. However, the long-term effects of the latter on adolescents' mental health are still little explored. Methods In the present natural experiment, we investigated these effects using longitudinal data collected before and after the first lockdown in Switzerland. Data come from 674 Swiss adolescents (56.7% females, Mage = 14.45, SDage = 0.50) during Spring 2019 (T1) and Autumn 2020 (T2) as part of the longitudinal MEDIATICINO study. Self-reported mental health measures included somatic symptoms, inattention, anxiety, irritability, anger, sleep problems, obsessive-compulsive symptoms, loneliness, and depression. Measures for screen-media activities included time spent on the Internet, smartphones, social media, video gaming, instant messaging, and television viewing. They were all assessed at T1 and T2. Results Paired-sample t-tests with Bonferroni's correction showed that most mental health problems increased over time with an overall medium effect size (Hedge's g = 0.337). In particular, medium effect sizes were found for anxiety, depression, and inattention; small-to-medium effect sizes were reported for loneliness, sleep problems, and obsessive-compulsive symptoms; and a small effect size was found for somatic symptoms. Screen-media activities increased, with the exception of television viewing and video gaming. The results of the hierarchical regression analyses showed that, controlling for covariates, increased time spent on social media – calculated as the difference between T2 and T1 – was the only screen-media activity significantly associated with worse mental health at T2 (β = 0.112, p = 0.016). More time spent in structured media activities like television viewing diminished levels of inattention (β = −0.091, p = 0.021) and anxiety (β = −0.093, p = 0.014). Among covariates, being female, experiencing two or more life events, having mental health problems at T1, and using screens for homeschooling negatively influenced mental health at T2. Conclusion These results align with literature indicating a small but negative effect of social media time on mental health. Underlying mechanisms are manifold, including increased exposure to COVID-19 news, heightened fear of missing out, social comparison, and time-displaced for activities such as physical activity and green time. However, in line with the structured days hypothesis, getting involved in media-structured activities like television viewing might protect against mental health symptoms.